The Influence of Cultural, Religious, and Health Factors on Recreational Facility Design Preferences in Lau Debuk-debuk, Karo Regency - Stefany Yulianda Colia; Isnen Fitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Lau Debuk-debuk is one of the tourist destinations for hot springs recreation located in Karo Regency, North Sumatra. Despite being popular among both local and international tourists, the existing hot spring facilities in the region still fall short of accommodating the cultural norms and religious practices of their diverse visitors, especially with regard to gender separation in bathing areas. This situation underscores the need for a deeper understanding of how cultural expectations and religious obligations affect spatial preferences. To address this issue, this study aims to investigate the influence of cultural and religious values on visitor preferences in designing gender-segregated hot spring facilities in Lau Debuk-Debuk, using a quantitative approach. It was employed by distributing structured questionnaires to 114 individuals who had previously visited the Lau Debuk-Debuk hot spring area. Given the increasing diversity of visitors to Lau Debuk-Debuk, understanding the link between cultural and religious values and facility design has become essential for creating inclusive tourism spaces. The responses were analyzed using descriptive and inferential statistical methods, including the Spearman correlation test, to explore the strength of relationships between cultural, religious, and health factors in facility design preferences. The results indicate that both cultural values and religious beliefs significantly affect visitor expectations, particularly regarding the need for gender-segregated spaces. The majority of respondents—both local and international—expressed a strong preference for facilities that uphold privacy, modesty, and respect for religious or traditional customs. These results emphasize the significance of incorporating culturally sensitive and Sharia-compliant design approaches in developing hot spring resorts. Taking these aspects into account not only improves visitor comfort and satisfaction but also contributes to creating inclusive and respectful tourism infrastructure that reflects the values of its intended users.